The Implications of Islamic Thought on Life for Biology Learning Design in Madrasah Aliyah - Rani Noho; Wirda AZ Umagap; Muhammat Mat Doan; Sahjad M Aksan (Golden Ratio of Social Science and Education, 2026)
Islamic thought views life as a trust from Allah, containing the values of monotheism, ethics, and human responsibility as caliphs on earth. This perspective has important implications for learning Biology in Madrasah Aliyah, which substantially studies the phenomena of life. This study aims to analyze the implications of Islamic thought on life for the design of biology learning in Madrasah Aliyah. This study used a descriptive qualitative approach with a field study type. The research subjects included biology teachers, Islamic Religious Education teachers, and 11th-grade students. Data were collected through classroom observations, in-depth interviews, and documentation studies, and then analyzed using Miles and Huberman’s interactive model.. The research results indicate that teachers have a normative understanding of life from an Islamic perspective, but this understanding has not yet been fully internalized systematically in the design of biology learning. The integration of Islamic values is still partial and has not been explicitly formulated in the objectives, methods, and evaluation of learning processes. This study concludes that Islamic thought on life needs to be used as a philosophical and pedagogical foundation in the development of biology learning designs so that learning is not only oriented toward mastering scientific concepts, but also toward fostering students' spiritual awareness and life ethics.